The Existence of Culinary at Lomban Festival in Jepara: Comparative Study of the Dutch East Indies and Reformation Period - Indrahti, Sri; Prasetyawan, Yanuar Yoga; Alamsyah, Alamsyah; Maziyah, Siti (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
In Jepara, various cultural activities are conducted regularly every year. This cultural activity is always accompanied by a culinary presentation in accordance with the activities, needs, and interests. One of the cultural activities in Jepara is the lomban festival. In this local tradition, a variety of culinary is presented as complement to the cultural activities. The culinary consists of various types, such as market snacks and complete food with rice, vegetables, and side dishes. The culinary in this lomban activity is described in sequence and detail. The culinary depicts the belief, symbolic and spiritual meaning of the supporters of that culture. Through this study, various types of culinary in cultural activities are well described including the symbolic and spiritual meaning behind the culinary presentation.